Pyrite oxidation with ozone: stoichiometry and kinetics. (3rd July 2018) - Rodríguez-Rodríguez, C.; Nava-Alonso, F.; Uribe-Salas, A.
ABSTRACT: One of the most frequent causes of refractoriness in precious metals leaching is their occlusion or fine dissemination into a pyritic matrix. This study experimentally explores the acid leaching of pyrite with ozone, suggests the stoichiometry of the reaction, estimates its activation energy and defines the effect of the main variables on the leaching kinetics. The results of stoichiometry tests allow establishing that one mole of pyrite requires 7.7 moles of ozone to produce one mole of ferric ion and 2 moles of HSO4 − ions. A decrease in the particle size, solution pH and solids' concentration of the leaching system increases pyrite dissolution. The type of acid (nitric, sulphuric and hydrochloric) does not affect pyrite dissolution rate. Up to 60% of pyrite is dissolved when the optimal experimental conditions are employed (1 g pyrite (−25 µm), 800 mL of 0.18 M of H2 SO4, 800 rev min −1, 1.2 L min −1 gas stream O2 /O3 with 0.079 g O3 L −1 and 25°C). The apparent activation energy of the pyrite-ozone reaction is 14.92 kJ mol −1, and the absence of a passive layer on the pyrite surface and the linearity of the dissolution profiles suggest that the dissolution kinetics is controlled by the chemical reaction.